Shifting the balance: conceptualising empowerment in individuals with spinal cord injury. (11th July 2016) - Rohatinsky, Noelle; Goodridge, Donna; Rogers, Marla R.; Nickel, Darren; Linassi, Gary
Abstract: Empowerment is believed to be an essential element in self‐management of disease and the promotion of self‐efficacy, and can be defined as the ability of individuals to increase control over aspects of their lives. In contrast, powerlessness in individuals with chronic illness can occur when they perceive that they lack the capacity, authority or resources to affect an outcome. Individuals with spinal cord injuries (SCIs) are at risk for powerlessness and have the potential to become empowered, but these concepts have not been explored within their context. The purpose of this study was to explore how individuals with SCI enact the empowerment process using Lord's (1991) process of empowerment framework. This study used a secondary analysis of a data set obtained from a mixed methods study exploring access to health and social care for 23 persons with SCI in Saskatchewan, Canada. The primary study data were collected from September 2012 to January 2013. The secondary analysis of data utilised a deductive thematic analysis approach and findings were conceptualised and applied to a model that represents the shift in balance between powerlessness and empowerment in individuals with SCI.